Analisis Yuridis Tindak Pidana Pemekorsaan; Studi Kasus Berdasarkan Berita Acara Pemeriksaan dari Laporan Polisi No. Pol: Lp/B/126/Vii/2025/Spkt/Res Malaka/Polda NTT - Samara, Finsensius; Kelore, Regina; Lende, Yoab; Therik, Brian Gabriel; Manurung, Yolanda Pricillia; Ressa, Merlindah Mooy; Theressa, Claudia (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This research analyzes the case of rape that occurred within the context of a dating relationship in Malaka Regency, East Nusa Tenggara, based on police report No.Pol: LP/B/126/VII/2025/SPKT/Res Malaka/POLDA NTT dated July 6, 2025. This case involves a suspect with the initials AB (21 years old) who raped his girlfriend, FA, in Kletek Forest on July 5, 2025, at 10:30 PM WITA. This research uses a normative legal research method with a case approach and descriptive analysis of the Examination Report (BAP) as the primary data source. The research findings indicate that: (1) this case is suitable to proceed to trial based on the presence of official reports, consistent victim testimony, supporting statements from three witnesses, medical evidence from the post-mortem examination, the suspect's confession, and physical evidence; (2) all elements of Article 285 of the Criminal Code have been cumulatively fulfilled; (3) the suspect was sentenced to 10 years in prison, considering several factors.